Fundamentals of construction estimating - Pratt, David J. 1946- (Cengage, 2019)
This comprehensive resource offers thorough instruction on the principles of construction estimating and helps readers develop the skills they need to become professional estimators. FUNDAMENTALS OF CONSTRUCTION ESTIMATING, Fourth Edition, presents estimating procedures in a straightforward and engaging way, clearly explaining key processes of estimating and costing construction work such as quantity takeoff; pricing of contractor work, sub-trade work, and site overhead; and compiling bid documents. In addition, the text includes drawings of two major projects--one residential and one commercial--to guide readers through a complete estimating process that can be followed by various trades on many different types of construction projects.